Enhancing Community Service through the Integration of the Student’s Role as an Agent of Change and Reuse Intention KKN Caption Design - Pipit Sari Puspitorini; Dwi Iryaning Handayani (Universitas Muhammadiyah Sidenreng Rappang, 2026)
Improving public satisfaction and reuse intention in social life requires new innovations, namely KKN. The KKN Blue Ocean Innovation integrated capstone design model integrates education, development, service, and community empowerment outside the campus environment. The proposed model, based on the stimuli-organism-response theory and the KKN framework, which integrates the four aforementioned student roles (catalyst, process helper, solution giver, and source linker) to study the intention reuse KKN. Valuable insights for implementing KKN to be accepted by the community are to prioritize community satisfaction as the object of study in integrating more innovative KKN concepts. Partial least squares structural equation modeling (PL-SEM) with a survey of 50 community members and students who have interacted and experienced community service (KKN) was used. Results: This study found that the solution giver dimension dominated the role of students as agents of change compared to the catalyst (C); process helper (PH); solution giver (SG); and sources linker (SL), which were 16%, 20%, 50%, and 14%, respectively. SL dominated the role of students as agents of change. The mediation analysis explains that community satisfaction mediates the relationship between the four dimensions and KKN reuse intention. The role of student agents of change includes raising community awareness and enthusiasm to change and develop SL for the better. The direct and indirect influence of the agent of change dimension on public satisfaction and reuse intention is a novelty of this study.